The impact of digital media on language development and communication competence among university students - Hashem, Rasha Adnan; Mahdi, Sulaiman Saleh (Research Journal in Advanced Humanities, 2025)
Recent decades have witnessed a significant expansion in the use of digital media as a primary means of daily communication, directly impacting language usage patterns and methods of social interaction. This paper studies the way of digital media platforms, like social media, messaging applications besides online forums, effect of language development also enhancing communication abilities of university students in both digital and real world. The digital communication increase having introduced novel phenomena of language, encompassing abbreviations, memes, emojis, in addition to code-switching that reflecting and reshaping language models. Lev Vygotsky's sociocultural theory is employed as theoretical framework that explains the interactive relationship between the individual and digital tools as cultural media that influence thought and language. Results indicate that digital media fosters creative language application and challenges traditional language conventions, affecting literacy and interpersonal skills. University student’s users, in particular, demonstrate a high degree of adaptability, developing shorthand and multimodal communication proficiency. However, concerns about decreased attention span, reduced in presence communication skills, and language deterioration are also discussed. The findings highlight the need for educational strategies that balance digital literacy with the cultivation of strong communication competencies, ensuring individuals can navigate digital and in presence communications effectively.